Tingkat Kesejahteraan Masyarakat Petambak Udang Vaname di Desa Mootinelo Kecamatan Kwandang Kabupaten Gorontalo Utara - Panamba, Novaldi; Baruadi, Alfi Syahri; Panigoro, Citra (Fakultas Kelautan dan Teknologi Perikanan - Universitas Negeri Gorontalo, 2023)
This study aims to determine the level of welfare of the vannamei shrimp farmers in Mootinelo Village, Kwandang District, North Gorontalo Regency. The sampling method used in this study is the saturated method (Census), which is the activity of collecting data and information by observing all elements of the specified population. With the research respondents as many as 32 people are farmers in Mootinelo Village, Kwandang District, NorthGorontalo Regency. Data were analyzed descriptively quantitatively and qualitatively supported by primary and secondary data. The results showed that the farming community in Mootinelo Village, Kwandang District, North Gorontalo Regency was included in the medium welfare category with a score of 1.80.